Factores de riesgo e incidencia en problemas de manguito rotador en deportistas de escalada entre 7 a 25 años, de la Federación Deportiva Los Ríos, Babahoyo período junio-octubre 2023. - Segura Salazar, Hillary Gabriela (2023)
The main objective of the project is to investigate the risk factors and the incidence of rotator cuff problems in rock climbing athletes aged 7 to 25, who are part of the Los Ríos Babahoyo Sports Federation during the period from June to October 2023. The project is based on identifying the risk factors associated with rotator cuff injuries in this specific population, including variables such as age, body mass index (BMI), anatomical alterations of the glenohumeral joint, and smoking habits. Additionally, other elements such as metabolic diseases, psychosocial status, manual tasks, and repetitive loads will be explored as possible contributors to rotator cuff injuries. The project also focuses on preventive physiotherapy as a key tool to mitigate these risks. It proposes the implementation of comprehensive musculoskeletal assessments, personalized training programs, and periodic preventive physiotherapy sessions to strengthen and maintain the health of the rotator cuff in athletes. The justification for this project lies in the high incidence of rotator cuff injuries in rock climbing athletes and the lack of updated research on their prevention and management in this specific population. It is expected that this proposal will have a significant impact on the health and performance of athletes, as well as on reducing the costs associated with rotator cuff injury treatment.